1984
DOI: 10.1126/science.6719137
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of N- myc in Untreated Human Neuroblastomas Correlates with Advanced Disease Stage

Abstract: A domain of DNA designated N-myc is amplified 20- to 140-fold in human neuroblastoma cell lines but not in cell lines from other tumor types. N-myc has now been found to be amplified in neuroblastoma tissue from 24 of 63 untreated patients (38 percent). The extent of amplification appears to be bimodal, with amplification of 100- to 300-fold in 12 cases and 3- to 10-fold in 10 others. Amplification was found in 0 of 15 patients with stage 1 or 2 disease, whereas 24 of 48 cases (50 percent) with stage 3 or 4 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
1,185
1
23

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,052 publications
(1,259 citation statements)
references
References 28 publications
(6 reference statements)
21
1,185
1
23
Order By: Relevance
“…17,24 Many poor-prognosis neuroblastomas are characterized by NMYC amplification. 7 A subset of NMYC -amplified neuroblastoma does not express caspase -8 because the CASP -8 gene is either deleted or silenced by methylation. 21,43 Because caspase-8 is part of the DISC initiating TRAIL signaling, TK /GCV will not cooperate with rhTRAIL in these neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…17,24 Many poor-prognosis neuroblastomas are characterized by NMYC amplification. 7 A subset of NMYC -amplified neuroblastoma does not express caspase -8 because the CASP -8 gene is either deleted or silenced by methylation. 21,43 Because caspase-8 is part of the DISC initiating TRAIL signaling, TK /GCV will not cooperate with rhTRAIL in these neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The original characterization of N-myc as a c-mycrelated gene (Stanton et al, 1986) was soon followed by reports of its ampli®cation in approximately onethird of cases of NBL, as well as by the observation that the degree of ampli®cation correlated inversely with prognosis (Brodeur et al, 1984(Brodeur et al, , 1985. These original ®ndings have generally been con®rmed in subsequent studies (Combaret et al, 1996;Rubie et al, 1997;Tsuda et al, 1997).…”
Section: Neuroblastoma (Nbl)mentioning
confidence: 97%
“…Loss of chromosome 1p material, occurring predominately through an unbalanced t(1;17) that also results in gain of 17q (Van Roy et al, 1994), is a common chromosomal imbalance found in NB and occurs preferentially in tumors with MYCN amplification (MNA) (Fong et al, 1989). All three of these nonrandom genetic abnormalities, loss of 1p, gain of 17q and MNA, are independently associated with a poor clinical outcome (Brodeur et al, 1984;Spitz et al, 2003;Attiyeh et al, 2005;Vandesompele et al, 2005).…”
mentioning
confidence: 99%